Hard times in the marvelous city : from dictatorship to democracy in the favelas of Rio de Janeiro - McCann, Bryan, 1968- (Duke University Press, 2014)
This history explains how and why the favelas of Rio de Janeiro were able to resist demolition in the 1970s but succumbed to the drug wars of the 1980s and 1990s.